Epistasis between type 2 diabetes susceptibility Loci on chromosomes 1q21-25 and 10q23-26 in northern Europeans. - Wiltshire, S; Bell, J; Groves, C; Dina, C; Hattersley, A; Frayling, T; Walker, M; Hitman, G; Vaxillaire, M; Farrall, M; Froguel, P; McCarthy, M (2006)
Characterisation of the interactions between susceptibility loci (epistasis) is central to a full understanding of the genetic aetiology and the molecular pathology of complex diseases. We have examined, in British and French pedigrees, evidence for epistasis between the type 2 diabetes susceptibility loci on chromosomes 1q21-25 and 10q23-26 using two complementary linkage-based approaches. Joint two-locus linkage analysis of 1q and 10q in British pedigrees provided significant evidence for interaction (P < or = 0.003) when comparing a general epistasis model with multiplicative or additive-effects-only models. Conditional linkage analysis (which models epistasis as a deviation from multiplicativity only) confirmed these findings, with significant LOD score increases at the 1q (P = 0.0002) and 10q (P = 0.0023) loci. These analyses provided sizeable reductions in the 1-LOD support intervals for both loci. Analyses of the British and French pedigrees together yielded comparable, but not enhanced, findings, with significant (P < or = 0.003) evidence for epistasis in joint two-locus linkage analysis, and during conditional linkage analysis significant increases in linkage evidence at the 1q (P = 0.0002) and 10q (P = 0.0036) loci. Our findings of epistasis nevertheless substantiate the evidence for genuine genetic effects at both loci, facilitate endeavours to fine-map these loci in population samples, and support further examination of this interaction at the nucleotide level by providing a robust prior hypothesis.